Antimicrobial Activity of Methanolic Extracts Of Cassia tora root - Dave, Dharmendra (International Journal of Pharmaceutical & Biological Archive, 2011)
Overuse of antibiotics has selected new strains of bacterial pathogens that are resistant to the very antibiotics used to combat them. Many plants have been used for centuries by traditional healers and may have antibacterial properties.it used in northern Nigeria in the treatment of ulcers, ring worm and other parasitic skin diseases. In cultures, the leaf extracts of the plant showed anti-bacterial activity. Antiviral activity, particularly against Newcastle disease virus and Vaccinia virus. Ciprofloxacin used as standard reference. Our research aim was to determine whether methanolic extracts obtained from the plant’s shoot could inhibit growth of gram-positive bacteria and gram- negative bacteria. The methanolic extracts were obtained using the soxhelet apparatus.